Adaptation of the Vaccine Prophylaxis Strategy to Variants of the SARS-CoV-2 Virus - Sofia M. Gulova; Uliana S. Veselkina; Irina V. Astrakhantseva (Vaccines)
The emergence of a novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus closely related to SARS-CoV and officially known as Betacoronavirus pandemicum precipitated a substantial surge in vaccine development that culminated during the global COVID-19 pandemic. At present, there are dozens of vaccines for the prevention of SARS-CoV-2 being utilized across the globe. However, only 10 of these vaccines have been authorized by the World Health Organization (WHO). These include mRNA-based, viral vector, subunit and whole-virion inactivated vaccines. At the current end of the pandemic, there has been a decline in the global vaccination rate, both for the general population and for those most at risk of severe illness from the virus. This suggests that the effectiveness of the vaccines may be waning. The decline occurs alongside a decrease in testing and sequencing for SARS-CoV-2. Furthermore, the process of tracking viruses becomes increasingly complex, thereby providing a selective advantage for SARS-CoV-2 and allowing it to evolve stealthily. In this review, we provide a comprehensive overview of viral evolution and vaccine development. We also discuss ways to overcome viral variability and test universal vaccines for all SARS-CoV-2 variants.